The effect of different parenting styles on the child behavior during the dental visit: observational longitudinal study - Sara Saiid Henedy; Amany M. Khalil; Sawsan Hafez Mahmoud; Laila Moustafa El-Habashy (BMC Oral Health)
Abstract Background It is widely recognized that parental influence significantly shapes children’s emotional health and behavioral patterns. The current study aims to evaluate the effect of different parenting styles on the child’s behavior during the dental visit. Methods Sixty healthy children age ranging from 4 to 6 years old who needed class I restoration in one of their primary molars were selected from the outpatient clinic of the Pediatric Dentistry and Dental Public Health Department, Faculty of Dentistry, Alexandria University, Egypt. Both parents signed a consent form to participate in the research and filled out the study questionnaires. Two questionnaires were used in this study: the Parenting Styles and Dimensions Questionnaire (PSDQ) and the demographic questionnaire to determine the parents’ socioeconomic status. The Frankl rating scale was used to evaluate the children’s behavior during the initial examination visit and the subsequent restorative visit. The procedure time was assessed from the videotaped restorative visit. Results The overall child behavior during the examination visit and the second restorative visit showed that children of authoritative parents demonstrated significantly positive behavior (Frankl rating 3) compared to the negative behavior in children of both authoritarian and permissive parents (Frankl rating 2) (P = 0.002, P = 0.004). The authoritative parenting style showed significantly less operative time than the authoritarian and permissive groups (P = 0.001, 0.008, respectively). Conclusion Children of authoritative parenting style showed significantly positive child behavior on the dental chair than those of permissive and authoritarian parenting styles.